Construction of Basic Network in Data Center Based on SDN Technology - Qiang Wu; Xin Xu; Guoyan Liu (Dianxin kexue)
By appling SDN technology in data center, the resource was aggregated to become an ability pool through abstracting the hardware resource by using the intelligent software, which makes network more like software and more agility, and provides automatic, safe, flexible and effective scheduling resources ability to meet the cloud computing data center. The solution makes up for the cloud computing in the short plate of network virtualization, makes calculation, storage and network more integrated, and realizes fully automated deployment of resource, real-time resource scheduling and rapid network troubleshooting, and has the potential to increase new business at any time, speeds up the network innovation rhythm, and provides a new option for cloud computing center operators to reduce the maintenance cost and improve user experience.